2007
DOI: 10.1177/1065912906298632
|View full text |Cite
|
Sign up to set email alerts
|

When Do Economic Sanctions Work?

Abstract: In this article, the authors examine perceptions of the salience of the issue under dispute by both sender and target states and their impact on sanction outcomes. They find that both the sender's perception of the salience of the issue and the asymmetry in perception of issue salience between sender and target favoring sender states have significant and dramatic effects on sanctions outcomes. This finding suggests that how states perceive the issue(s) at dispute matters in determining the likelihood of sancti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In addition, the type of issues at stake matters for the effectiveness of economic sanctions. Senders of economic sanctions are less likely to succeed for issues of high salience, for example, security-related matters (Ang and Peksen 2007;Drury and Li 2006;Li and Drury 2004;Morgan, Bapat, and Kobayashi 2014).…”
Section: Literature On Economic Sanctionsmentioning
confidence: 99%
“…In addition, the type of issues at stake matters for the effectiveness of economic sanctions. Senders of economic sanctions are less likely to succeed for issues of high salience, for example, security-related matters (Ang and Peksen 2007;Drury and Li 2006;Li and Drury 2004;Morgan, Bapat, and Kobayashi 2014).…”
Section: Literature On Economic Sanctionsmentioning
confidence: 99%
“…This work has shown that a number of factors, including the type of government a target state possesses, the costs the sanctions impose on their target, the type of sanctions imposed, their objective, and the length of time they persist, can affect sanctions outcomes (e.g., Hufbauer, Schott, and Elliott 1990;Drury 1998Drury , 2005Drezner 2000;Allen 2005;Ang and Peksen 2007;Hufbauer et al 2007;Lektzian and Souva 2007;Bapat, Heinrich, Kobayashi, and Morgan 2013). This work has shown that a number of factors, including the type of government a target state possesses, the costs the sanctions impose on their target, the type of sanctions imposed, their objective, and the length of time they persist, can affect sanctions outcomes (e.g., Hufbauer, Schott, and Elliott 1990;Drury 1998Drury , 2005Drezner 2000;Allen 2005;Ang and Peksen 2007;Hufbauer et al 2007;Lektzian and Souva 2007;Bapat, Heinrich, Kobayashi, and Morgan 2013).…”
Section: Economic Sanctions Spoiler Behaviors and International Insmentioning
confidence: 99%
“…Given the limited effectiveness of economic sanctions, much of the sanctions literature has focused on the factors associated with why they succeed or fail. This work has shown that a number of factors, including the type of government a target state possesses, the costs the sanctions impose on their target, the type of sanctions imposed, their objective, and the length of time they persist, can affect sanctions outcomes (e.g., Hufbauer, Schott, and Elliott 1990;Drury 1998Drury , 2005Drezner 2000;Allen 2005;Ang and Peksen 2007;Hufbauer et al 2007;Lektzian and Souva 2007;Bapat, Heinrich, Kobayashi, and Morgan 2013). Of particular salience to our inquiry is the work that has explored the role played by third-party states 3 in either undercutting the senders' sanctioning efforts or cooperating with them.…”
Section: Economic Sanctions Spoiler Behaviors and International Insmentioning
confidence: 99%
“…Economic coercion appears to work better at the threat stage than at the imposition stage (Nooruddin 2002; Drezner 2003). Sanctions are more likely to produce concessions when the target’s costs of sanctions imposition are significant (Dashti‐Gibson, Davis, and Radcliff 1997; Drezner 1999), when the issue under dispute is of low salience to the target country (Morgan and Schwebach 1997; Ang and Peksen 2007), when the sender and target did not anticipate frequent future conflicts (Drezner 2000), when an international institution endorses the sanctions (Drury 1998; Drezner 2000; Bapat and Morgan 2009), and when the target state is a democracy (Bolks and Al‐Sowayel 2000; Allen 2005).…”
Section: The Trouble With Sanctions—and the Sanctions Literaturementioning
confidence: 99%
“…It is not clear, however, whether financial statecraft be as successful on issues more highly valued by the target regime, however (Ang and Peksen 2007). Steil and Litan (2006:77) surveyed recent efforts by the United States to use capital market access to force policy changes in Sudan, Russia, and China.…”
Section: Assessing Smart Sanctionsmentioning
confidence: 99%